2008
DOI: 10.3113/fai.2008.1079
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of the Second Metatarsocuneiform Joint for the Painful Osteoarthrosis

Abstract: Fusion of the second MCJ is a moderately effective treatment for osteoarthrosis of the joint. In this series of patients, 74% were pain-free and nonunion was the most serious complication encountered, no patient was made worse by surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Later, Kilmartin et al provided a second TMTJ fusion for 23 patients with a dorsal 2.7 mm plate-and-screws. 16 While they observed significant improvements in patient foot function, they reported an incidence of bony nonunion at the fusion site as 13%. Later, Filippi et al performed midfoot fusions with plates-andscrews in 72 patients and reported a lower nonunion rate of 6.9%.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Later, Kilmartin et al provided a second TMTJ fusion for 23 patients with a dorsal 2.7 mm plate-and-screws. 16 While they observed significant improvements in patient foot function, they reported an incidence of bony nonunion at the fusion site as 13%. Later, Filippi et al performed midfoot fusions with plates-andscrews in 72 patients and reported a lower nonunion rate of 6.9%.…”
Section: Discussionmentioning
confidence: 98%
“…23,30 Patients with large areas of bone loss at their affected TMTJs were excluded from this investigation as these individuals require structural bone graft and typically need plate-andscrews for their arthrodesis. 16 To minimize confounding factors with postoperative wound complications, patients with prior surgery to their midfoot were also excluded. In addition, patients with lateral column midfoot arthritis that necessitated surgical treatment through a separate incision at the time of surgery were excluded (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation